GM-CSF-miRNA-Jak2/Stat3 Signaling Mediates Chemotherapy-Induced Cancer Cell Stemness in Gastric Cancer - Xiang, Xue; Ma, Hai-zhong; Chen, Ya-qiong; Zhang, Dong-zhi; Ma, Shi-xu; Wang, Hong-jing; Liu, De-ming; Yuan, Yuan; Cai, Hui (Frontiers in Pharmacology, 2022)
Chemotherapy serves as the first choice in clinic to treat advanced gastric cancer. However, emerging evidence indicated the induction of drug resistance and cancer stem cells (CSCs) occasionally by chemotherapy, which seriously limit the therapeutic effects, but the regulatory mechanism remains unclear. Here we treated two human gastric cancer cell lines SGC7901 and BGC823 with 5-Fluorouracil (5-Fu) or Cisplatin (DDP) in vitro. The survived cells showed significant increase of drug resistance, cell stemness and cytokine GM-CSF expression and secretion. As such, GM-CSF was applied to stimulate gastric cancer cells, followed by CD133+ CSC analysis, sphere formation assay and stemness gene expression analyses. As a result, CSCs showed induction by GM-CSF treatment. A gastric cancer animal model further indicated promotion of tumor growth after GM-CSF treatment in vivo. High-through miRNA screening analyses identified a subset of miRNAs under regulation of both 5-Fu and GM-CSF in gastric cancer cells, including upregulation of miR-877-3p. Targeted overexpression or knockdown of miR-877-3p in gastric cancer cells revealed the oncogenic function of miR-877-3p in regulating gastric cancer by suppressing target gene SOCS2. Jak2/Stat3 signaling pathway, as a downstream target of SOCS2, showed activation in vitro and in vivo after treatment with miR-877-3p or GM-CSF. Our findings not only revealed a novel mechanism through which chemotherapy induced CSCs in gastric cancer via GM-CSF-miRNA-Jak2/Stat3 signaling, but also provided an experimental evidence for appropriate dose reduction of adjuvant chemotherapy in treatment of cancer patients.